Pengaruh Pelaksanaan Ramp Check terhadap Keselamatan Penerbangan di Terminal II Bandar Udara Soekarno-Hatta - Sarinah Sarinah; Ajeng Oktavianah Putri; Irza Tanjung (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
The purpose of this research is to identify the influence of flight safety ramp check implementation in Terminal II Soekarno Hatta airport in 2017. The method applied in this research was quantitative method using simple linier regression, correlation coefficient analysis, and hypothesis testing to analyze the data. The result shows that there is a proportional relation of the ramp check implementation towards the flight safety. This can be seen from the simple linier line equationwhich is Y = 29,754 + 0,524 X. The analysis also shows a strong relation of the ramp check implementation towards the flight safety that can be seen from the coefficient correlation r= 0,406, and the hypothesis testing tcount= 2,130 > ttable= 1,714 thus HO is rejected and Hais accepted. This means that there is a significant influence of flight safety ramp checkimplementation in Terminal II SoekarnoHatta airport.